Endovascular management of suprascapular artery pseudoaneurysm - Prater, Scott (Baylor Health Care System, 2010)
Pseudoaneurysms can be debilitating for patients and occasionally life threatening. Many imaging modalities may be used to assess and define these vascular lesions, and various methods have been employed in their treatment. Our patient suffered trauma to his left shoulder resulting in fracture of his clavicle following an automobile accident and subsequently was found to have a pseudoaneurysm of his left suprascapular artery on imaging. This was treated by transarterial embolization, which resulted in immediate relief of his symptoms. Endoluminal management offers a safe and effective way of treating these lesions.